KADAR TRIGLISERIDA MENCIT SETELAH PEMBERIAN AIR PERASAN DAUN KETEPENG (Cassia alata) - Adhy Nugroho, Christianto (Widya Warta, 2019)
The extraordinary development of technology makes all human needs can be afforded easily by gadgets. The exixtence of gadgets can reduce human physical activities that lead to health assault, namely dylipidemia. Increasing or decreasing fat fractions in blood vessels is one of its symptoms. One of the fat fractions is trigycerides. The ketepeng plant which contains active substance such as flavonoids, tannis, and saponine have been widely used for medical treatment. This study aimed to determine the ability of ketepeng juice in reducing triglyceride levels.In this study, the tested animals in group 1 were treated with high-fat feed, the ones in group 2 were given high-fat feed, and the ones in group 3 were given high-fat feed and ketepeng leaf juice concentration of 25% (w / v), namely 0.5 ml / 20 grams BW. The results showed that the juice of ketepeng leaves could reduce the triglyceride levels of mice.